Engaging Engagement: Critical Reflections on a Canadian Tradition - Waldram, James B. (Anthropologica, 2022)
In this revised address for the 2009 Weaver-Tremblay Award, I critically examine the notion of "engaged" anthropol? ogy as it has emerged, especially in the United States, and I argue that engagement has been a long-standing feature of Canadian anthropology which predates this contemporary devel? opment. I do so by briefly reviewing some of the major initia? tives in Canadian anthropology, and especially applied anthro? pology during the 1970s and 1980s, and suggest that in Canada we did not experience the divisive debate over theoretical ver? sus applied anthropology that characterized the U.S. and ren? dered applied anthropology a weaker sub-discipline in the eyes of many. I conclude by arguing for a need to celebrate how Cana? dian anthropology has been on the leading edge of engaged anthropology for decades.